Research on Lightweight Technology of Hydraulic Components for Integrated Fast Reactor Main Pump - PU Enshan1, ZHAI Xiao1, GU Jipin1, LIU Simin1, ZHANG Xu2 (Yuanzineng kexue jishu)
To meet the requirements of our country’s nuclear energy development and defense technology industry development, and to achieve national carbon neutrality and energy security needs, it is necessary to comprehensively break through and master the key technologies of integrated nuclear energy systems. As an important dynamic equipment in integrated fast reactors, the primary circuit main pump has been autonomous, but its weight is too heavy. In order to improve its economy, lightweight research needs to be carried out. Through the comparative analysis of the main pump structural schemes between China and Russia, the main similarities and differences of the two main pumps were identified. Based on the weight differences of the main components, the requirement for lightweight of the hydraulic components of the integrated fast reactor main pump was clarified. According to the hydraulic design requirements of the integrated fast reactor main pump, the optimization idea for lightweight of the hydraulic components was clarified. The hydraulic performance of different numbers of suction ports (10, 6, and 4) was analyzed using CFD numerical simulation methods. On the premise of ensuring that the hydraulic performance meets the requirements, the optimization scheme was determined. According to the CFD analysis results, as the number of suction ports decreases, the hydraulic efficiency gradually decreases, and the weight also decreases accordingly. When the number of suction ports is reduced to 4, the outlet flow field is poor. Since the scheme with 10 suction ports is too heavy, and the scheme with 6 suction ports has a significant weight reduction effect at the cost of slightly sacrificing efficiency, the final design scheme was determined to be the 6-suction-port scheme.